TINJAUAN YURIDIS TERHADAP KEBEBASAN BERSERIKAT, BERKUMPUL DAN MENGELUARKAN PENDAPAT BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2013 TENTANG ORGANISASI KEMASYARAKATAN - RAJA ADIL SIREGAR; Emilda Firdaus; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In the new law was passed precisely on July 22, 2013 last, great hope in thecommunity contribute significantly to regulate the scope and definition of SocialOrganization clearly related to administrative legal aspects. Although equipped withsetting role of government and local government in fostering Community Organization,the presence of foreign Community Organizations conducting activities in Indonesia, tothe sanctions for Community Organization who commit certain violations. So when anorganization Kemasyarakatanyang no legal status, have registered to be recognized asCommunity Organisations who can do the organization's activities in the sphere ofregional and national.Instead of a Community Organisations who do not enroll in governmentauthorities can not service of the government, but the state can not establish theCommunity Organization as an illegal organization, even the state can not prohibit suchactivities as long as not violating the law. But if the events and activities of CommunityOrganizations has been proven to have violated the law and threaten security and publicorder, violate the rights of freedom of others, as set forth in the sense of freedom ofhuman rights, or violate the moral values and religion, the state is obliged to ensurepublic order and function can perform law enforcement, can even stop the activities of aCommunity Organization.The explanation was clearly gives understanding to the state or the ruling for notlimiting step and Social Organization activities based solely on their registration status.In addition, the right of individuals to participate in advancing the nation through anorganization or association as prescribed in Article 28E paragraph (3), which in essencestates must respect these rights. Preferably Act No. 17 of 2013 on Social Organizationrevisions back, because there are many chapters which give rise to a contradiction to theother rules. For Community Organisations who are not registered are still allowed tocarry out activities, just not getting Social and Development funding from theGovernment.Keywords: Freedom of Association, Assembly and Removing Opinion Based on LawNo. 17 of 2013 on Social Organization